Efficacy of Combined in-vivo Electroporation-Mediated Gene Transfer of VEGF, HGF, and IL-10 on Skin Flap Survival, Monitored by Label-Free Optical Imaging: A Feasibility Study - Seyed Jafari, S. Morteza; Blank, Fabian; Ramser, Hallie E.; Woessner, Alan E.; Shafighi, Maziar; Geiser, Thomas; Quinn, Kyle P.; Hunger, Robert E.; Gazdhar, Amiq (Frontiers in Surgery, 2021)
Preventing surgical flaps necrosis remains challenging. Laser Doppler imaging and ultrasound can monitor blood flow in flap regions, but they do not directly measure the cellular response to ischemia. The study aimed to investigate the efficacy of synergistic in-vivo electroporation-mediated gene transfer of interleukin 10 (IL-10) with either hepatocyte growth factor (HGF) or vascular endothelial growth factor (VEGF) on the survival of a modified McFarlane flap, and to evaluate the effect of the treatment on cell metabolism, using label-free fluorescence lifetime imaging. Fifteen male Wistar rats (290–320 g) were randomly divided in three groups: group-A (control group) underwent surgery and received no gene transfer. Group-B received electroporation mediated hIL-10 gene delivery 24 h before and VEGF gene delivery 24 h after surgery. Group-C received electroporation mediated hIL-10 gene delivery 24 h before and hHGF gene delivery 24 h after surgery. The animals were assessed clinically and histologically. In addition, label-free fluorescence lifetime imaging was performed on the flap. Synergistic electroporation mediated gene delivery significantly decreased flap necrosis (P = 0.0079) and increased mean vessel density (P = 0.0079) in treatment groups B and C compared to control group-A. NADH fluorescence lifetime analysis indicated an increase in oxidative phosphorylation in the epidermis of the group-B (P = 0.039) relative to controls. These findings suggested synergistic in-vivo electroporation-mediated gene transfer as a promising therapeutic approach to enhance viability and vascularity of skin flap. Furthermore, the study showed that combinational gene therapy promoted an increase in tissue perfusion and a relative increase in oxidative metabolism within the epithelium.